2019
DOI: 10.1007/s00018-019-03074-9
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1 regulates neuroglial cell mediating Aβ clearance via the epigenetic regulation of endocytosis-related genes expression

Abstract: The accumulation of intracellular β-amyloid peptide (Aβ) is important pathological characteristic of Alzheimer’s disease (AD). However, the exact underlying molecular mechanism remains to be elucidated. Here, we reported that Nuclear Paraspeckle Assembly Transcript 1 (NEAT1), a long n on-coding RNA, exhibits repressed expression in the early stage of AD and its down-regulation declines neuroglial cell mediating Aβ clearance via inhibiting expression of endocytosis-related genes. We find that NEAT1 is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
111
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 61 publications
2
111
0
Order By: Relevance
“…The rescuing effects of metformin further confirmed by in-vivo studies. In our previous study, we detected the mRNA levels of Neat1 in 3-month-old APP/PS1 double transgenic mouse, and found reduced Neat1 expression compared with C57 mice [16]. In present study, these nearly 3 months old AD mice were observed an increased in the level of Neat1 and Fzd3 mRNA in the hippocampus of metformin treated group compared to control group treated with ddH2O (Fig 6B and C).…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…The rescuing effects of metformin further confirmed by in-vivo studies. In our previous study, we detected the mRNA levels of Neat1 in 3-month-old APP/PS1 double transgenic mouse, and found reduced Neat1 expression compared with C57 mice [16]. In present study, these nearly 3 months old AD mice were observed an increased in the level of Neat1 and Fzd3 mRNA in the hippocampus of metformin treated group compared to control group treated with ddH2O (Fig 6B and C).…”
Section: Resultssupporting
confidence: 65%
“…The down-regulation of NEAT1 expression contributed to amyloid-β deposition, via inhibiting expression of multi endocytosis related genes. Through interaction with P300/CBP complex, NEAT1 regulated expression of these genes via affecting H3K27 acetylation (H3K27Ac) and H3K27 crotonylation (H3K27Cro) in the promotor region of these genes[16]. In this investigation, we found that NEAT1 involves AD progression also through dysregulation of glycolysis and up-regulation of p-tau.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…It has previously been shown that multiple PTM amyloid‐β peptides were observed in the brain of AD patients 29 . For example, in a previous study, it was demonstrated that acetylation and crotonylation of histones potentially influenced Aβ1‐42, thereby regulating the pathology of dementia 30 . Moreover, several strategies have been developed to inhibit Aβ aggregation or to promote Aβ clearance for the prevention and treatment of BCCAO‐induced cognitive impairment 31‐33 .…”
Section: Discussionmentioning
confidence: 99%